Identificação de polimorfismos no gene APOE em pessoas idosas com queixas cognitivas da cidade de São Carlos,SP- Brasil - Rozendo, Fernanda Carolina (2023)
The increasing aging of the world's population has resulted in a significant increase in chronic noncommunicable diseases, including those that cause dementia. The complaint of memory loss in the elderly may initially manifest as (i) subjective cognitive decline (SCD) or as (ii) mild cognitive impairment (MCI). Alzheimer's disease (AD) accounts for more than half of all cases of dementias. There are several genetic risk factors associated with AD, with the polymorphism found in the Apolipoprotein E (APOE) gene being one of the most studied. In this study with a sample of 25 elderly with cognitive complaints from the city of São Carlos-SP (7 with AD and 18 with cognitive complaints without dementia), we sought to identify polymorphisms in the APOE gene that may be associated with the development of AD. Of the patients with AD, two presented the APOE4 isoform; in the group of patients with cognitive complaints without dementia these polymorphisms were not found. However, three of the people with cognitive complaints without dementia had other polymorphisms already described as rs769455 (n=2) and rs557715042 (n=1) in the APOE gene. There are few reports in the literature associating these last two polymorphisms with AD and none associated with cognitive complaints without dementia. Identification of these markers may contribute to early diagnosis and aid in the development of treatment strategies.